1989
DOI: 10.1111/j.1445-2197.1989.tb01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Lobular Mastitis

Abstract: The clinical and histological features of six cases of granulomatous lobular mastitis are presented. All six patients were parous, 1–6 years after their last pregnancy with a mean age of 34 years; all had unilateral disease and presented with an extra‐areolar breast lump. Histologically, all demonstrated a non‐caseating granulomatous inflammatory condition centred on breast lobules; in four women there was an acute inflammatory process with micro‐abscess formation. Five of the six cases had persistent or recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…Relapse rates after wide local excision are reported to be 6-83% (23,42). The diversity of these rates can be explained by the absence of a standard surgical procedure and the scantiness of follow-up periods and number of cases.…”
Section: Figure 2 Mammographic Imaging Of the Breast Before Treatmenmentioning
confidence: 99%
“…Relapse rates after wide local excision are reported to be 6-83% (23,42). The diversity of these rates can be explained by the absence of a standard surgical procedure and the scantiness of follow-up periods and number of cases.…”
Section: Figure 2 Mammographic Imaging Of the Breast Before Treatmenmentioning
confidence: 99%
“…This can result in the development of a mammary fistula, as described by our patient, leading to a chronic situation. This situation can be distinguished from granulomatous mastitis, which is defined by a typical histological aspect, and for which various aetiologies are put forward including autoimmune processes, as bacteria are rarely isolated from granulomatous mastitis (Galea et al, 1989). Abscesses should be treated with antibiotics, but granulomatous mastitis is usually treated with steroids.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies reporting that, along with wide local excision, with prednisolone treatment the rate of relapse of disease are low (3,9,18). In some studies it is reported that the relapse rate is up to 80% after local excision separately (18,19). Oral prednisolone is often administered as a substitute to surgical treatment or in the cases when remission is not achieved (17).…”
Section: Discussionmentioning
confidence: 99%